The Communist Presence in Guatemala and El Salvador. The Look of the Guatemalan Ministry of Foreign Affairs (1929-1932) - Taracena Arriola, Arturo (2022)
The existing files in the Foreign Relations section of the General Archive of Central America on communism in the region for the years 1929-1932 (B-99-30-6, 6724 and B-99-30-6, 6725), have allowed me to see that it is necessary to rethink the role of the Communist International and its international agents in the events that had their central point in the peasant insurrection in El Salvador. An insurrection that recent studies have been able to show was produced by structural causes that affected the peasantry of western Salvador, whose radicalization created points of contact with the Salvadoran Communist Party and International Red Aid.